Analysis of the Piecework Pay System in Improving Work Performance Productivity in the Construction of SMK School Buildings in Caruban District, Madiun Regency - Riyadi, Slamet; Tjendani, Hanie Teki; Wulandari, Esti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The application of the piece-rate wage system in construction projects has the potential to influence project timeliness and worker motivation. This study examines the effect of the piece-rate wage system on the completion efficiency of the SMK school building project in Caruban District, Madiun Regency. A quantitative approach was used, with multiple linear regression analysis conducted on data collected from 40 construction workers via questionnaires. The study analyzed the impact of wage systems, work communication, and work environment on labor productivity and motivation. The results showed that these three factors significantly influence the timely completion of construction work, with the piece-rate wage system playing a crucial role in enhancing worker performance. The findings highlight that implementing a structured piece-rate payment model, improving communication between workers and supervisors, and ensuring a conducive work environment can optimize labor efficiency. This study suggests that contractors and project managers should adopt clear wage agreements, provide incentives for quality work, and establish monitoring mechanisms to balance productivity with work quality.